Sapient : defining success was both the challenge and the opportunity - Nagy, Andrea, (SAGE knowledge. Cases., 2016)
Although Sapient was categorized as a marketing, business, and technology consulting company, employees insisted that they never sold consulting or provided mere deliverables. Instead, Sapient promised "client success" and to this end had articulated a model with three principles that the company perceived as central to its value proposition. For Sapient, 'client success' was not a rhetorical gesture or a marketing slogan but a philosophy that permeated the way the company approached every client. Maintaining a client focus was one of the core values that the co-founders of Sapient, Jerry Greenberg and Stuart Moore, articulated soon after they started their technology consulting company in 1990.